2013
DOI: 10.1111/str.12033
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Identification of CFRP Viscoelastic Models from Creep to Dynamic Loadings

Abstract: Rate‐dependent models require creep or mechanical tests at various strain rates in order to be identified and validated. Different geometries coexist for creep and static tests (normative geometry) and for dynamic tests. Therefore, due to geometrical sample considerations, experimental results could be inconsistent for identification or validation procedures, inducing, for example, differences on the shear modulus only due to the change of geometry. The objective of this work is to present an improved sample g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…Berthe et al [29] conducted high rate coupon testing on T700GC/M21 material which showed the shear modulus increased by 40% when the loading rate was increased from 10 -3 −1 to 88 −1 but no discernible change in the transverse modulus. This suggests that the ply configuration is the cause of the apparent rate independence observed in this study.…”
Section: Strain Rate Independencementioning
confidence: 99%
“…Berthe et al [29] conducted high rate coupon testing on T700GC/M21 material which showed the shear modulus increased by 40% when the loading rate was increased from 10 -3 −1 to 88 −1 but no discernible change in the transverse modulus. This suggests that the ply configuration is the cause of the apparent rate independence observed in this study.…”
Section: Strain Rate Independencementioning
confidence: 99%
“…In Berthe's work, the same discrepancies in the nonlinear domain were observed between Type A and B specimens. No inconsistencies were observed in the viscoelastic range, however, which was the main focus of the authors' studies.…”
Section: Specimen Reductionmentioning
confidence: 53%
“…All dimensions are summarized in Table . Concerning the viscoelastic part of the response, Type B specimens are able to ensure the representativity of Type A specimens with a free length set to only twice the width and a further reduced section . Section reduction is however not considered in this study.…”
Section: Specimen Reductionmentioning
confidence: 99%
See 2 more Smart Citations